Binding of Divalent Cations to Insulin: Capillary Electrophoresis and Molecular Simulations - Duboué-Dijon, Elise; Delcroix, Pauline; Martinez-Seara, Hector; Hladílková, Jana; Coufal, Pavel; Křížek, Tomáš; Jungwirth, Pavel (The journal of physical chemistry. B, 2018)
In the present study, we characterize the binding of divalent cations to insulin in aqueous salt solutions by means of capillary electrophoresis and molecular dynamics simulations. The results show a strong pH dependence. At low pH, at which all the carboxylate groups are protonated and the protein has an overall positive charge, all the cations exhibit only weak and rather unspecific interactions with insulin. In contrast, at close to neutral pH, when all the carboxylate groups are deprotonated and negatively charged, the charge-neutralizing effect of magnesium, calcium, and zinc, in particular, on the electrophoretic mobility of insulin is significant. This is also reflected in the results of molecular dynamics simulations showing accumulation of cations at the protein surface, which becomes smaller in magnitude upon effective inclusion of electronic polarization via charge rescaling.
Keywords: Magnesium; Molecular Dynamics Simulation; hořčík; Electrophoresis, Capillary; Hydrogen-Ion Concentration; elektroforéza kapilární; vazba proteinů; lidé; Zinc; simulace molekulární dynamiky; kationty dvojmocné; Insulin; vápník; voda; zinek; Water; Calcium; inzulin; koncentrace vodíkových iontů; Protein Binding; Cations, Divalent; Humans